Isolasi, Karakterisasi, dan Identifikasi Bakteri Penghasil Hemolisin dari Penderita Gingivitis: Isolation, Characterisation, and Identification of Hemolysin-Producing Bacteria from Gingivitis-Diagnosed Patient - Sutandi, Michellia Salmaa Ashilla; Budiarti, Sri; Priyanto, Jepri Agung (Departemen Biologi, Institut Pertanian Bogor, 2024)
Gingivitis is a gum inflammation caused by pathogenic bacterial infection. One of the virulence factors of pathogenic bacteria is hemolysin which plays an important role in lysing the red blood cells. This study aimed to isolate, characterise, and identify hemolysin-producing bacteria from a gingivitis-diagnosed patient. Quantification of the bacterial growth in blood agar base media showed that the number of bacteria on the gums of gingivitis patient was 1.63 × 107 CFU/ml. Seven bacterial isolates with different colony and cellular morphology were selected. Of 7 isolates, 3 isolates were β hemolytic, 3 isolates α hemolytic, and 1 isolate non-hemolytic. Six isolates with hemolytic activity were selected for colony and cellular morphology characterisation. Based on Gram-staining procedure, all six isolates belong to bacilli Gram-positive bacteria. Molecular identification with 16S rRNA gene revealed that these isolates were closely related to Bacillus spp., such as Bacillus cereus, Bacillus altitudinis, and Bacillus tequilensis.